CONSTRUÇÃO DE UM SISTEMA DE BAIXO CUSTO COM ALTA FREQUÊNCIA DE AQUISIÇÃO DE DADOS PARA CRONOPOTENCIOMETRIA - Lázaro J. Dalla Costa Jr.; Ernesto C. Pereira (Química Nova, 2015)
This work reports the building of a low-cost experimental setup for high temporal resolution data acquisition. The setup is useful for different applications, especially for voltage data acquisition during electrochemical experiments. The proposed setup performed two hundred thousand measurements per second (5 µs time resolution) and revealed unknown curve characteristics during chronopotentiometry of the anodization of valve metals. This information can serve as a starting point for further investigations on the nature of voltage oscillations in the breakdown region during valve metal anodization.